PENYELESAIAN SENGKETA TANAH TIAKUR IBUKOTA KABUPATEN MALUKU BARAT DAYA PROVINSI MALUKU: STUDI KASUS: PUTUSAN MAHKAMA AGUNG NOMOR 1835 K/PDT/2019 - Lewier, Samuel Porsiana; Borman, M. Syahrul; Subekti, Subekti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Soil, as one of the vital aspects for human survival, has a very important role. The presence of land provides great potential in producing natural resources that provide significant benefits to many people. However, the importance of land also means that the amount is limited, and therefore, there needs to be regulation from the government. Disputes over land ownership and use often arise in communities, and this problem is tapering from year to year, spreading in almost all parts of Indonesia, including both urban and rural areas. One example that illustrates this condition can be found in the community of Tiakur, the capital of Southwest Maluku Regency, Maluku Province, as exemplified in Supreme Court Decision Number 1835 K / Pdt / 2019. The researcher formulates questions based on this background: (1) What is the judge’s consideration for the settlement of the land dispute in Tiakur, the capital of Southwest Maluku Regency, Maluku Province? (2) How is the settlement of the land dispute in Tiakur, the capital of Southwest Maluku Regency, Maluku Province? The method used is Normative research with a statutory approach and a case approach, using descriptive analysis techniques, the results of the study show, that the judex facti decision / Ambon High Court in this case is not contrary to the law and / or the law, then the cassation application submitted by Cassation Applicant Frits Hosea Gaspar Pooroe, must be rejected. 2. Tiakur Land The capital of Southwest Maluku Regency of Maluku Province is a former Toinaman State lordship covering an area of ± 4000 Ha (Hecto Are), located in West Moa, Moa District, Southwest Maluku Regency, which has been granted/released by the defendants to the Southwest Maluku Regency Government